Sectoral Shocks and Spillovers : An Application to COVID-19 - Das, Sonali; Magistretti, Giacomo; Pugacheva, Evgenia; Wingender, Philippe (Washington, D.C. : International Monetary Fund, 2021)
This paper examines the role of sectoral spillovers in propagating sectoral shocks in the broader economy, both in the past and during the COVID-19 pandemic. In particular, we study how shocks that occur within a sector itself and spillovers from shocks to other sectors affect sectoral activity, for a large sample of countries from 1995 to 2014. We find that both supply and demand shocks-measured as changes in, respectively, productivity and government purchases at the sector level-have large spillover effects on sector-level gross value added and on a sector's share of the economy. We then use these historical estimates, together with the network structure of global production, to quantify the spillovers from the economic shock associated with the pandemic. We find spillover effects to be sizeable, making up a significant fraction of the overall decline in activity in 2020.Our results have implications for the design of policies with a sectoral dimension.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Business Fluctuations; Cycles; Externalities; General Equilibrium and Disequilibrium; Macroeconomic Aspects of International Trade and Finance